Placenta Previa. Specialized Maternal Perinatal Institute - Oscanoa, Aníbal (2015)
OBJETIVE: To identify the clinical and epidemiological of pregnant women who have placenta previa (PP) features. DESIGN: Descriptive, prospective and transversal study. PLACE: Specialized Maternal Perinatal Institute (IME), Department of Obstetrics. MATERIALS AND METHODS: 59 cases of PP checked by ultrasound and caesarean section were presented. RESULTS: Rates: cumulative incidence 0.63% and 3.39% fetal lethality, was 44% complete central PP and 33.9% marginal; the most affected age group was 20 to 35 with 69.8% of cases; 69.5% had prenatal care; 79.7% were multiparous; 52.5% completed his term gestation and 42.4% between 29 and 36 weeks. Clinical features, 72.9% started bleeding spontaneously, 25% bled abundantly and 52.5% painless. The risk of placenta previa in women over 34 years was OR = 2.03 and OR = 3.31 previous cesarean. 100% of cases ended with segmental caesarean and 5 of them, plus hysterectomy. Urinary infection and anemia were the most frequent complications before and after operative delivery. CONCLUSIONS: We found that the etiologic factors were mostly associated history of curettage (40.7%), previous cesarean section (33.9%) and aged (28.8%) pregnant; represented high frequencies compared to those found in the literature; It is explained by the higher frequency of this background in our pregnant and volume we serve.